2014
DOI: 10.2753/sor1061-0154530404
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Age in Demography and Today's Older Generation

Abstract: Data on perceptions of age and employability in Russia show that attitudes are a barrier to better utilization of human capital, and that Russia's economic and social future will depend on its ability to change attitudes and employment practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Earlier research has suggested that lifespan changes, like decreasing mental as well as physical reserves, can significantly affect the reported levels of employability (Brooke and Taylor, 2005;Ng and Feldman, 2009;Vandenberghe et al, 2012;Nilsson and Ekberg, 2013;Rusanova, 2014;Bal and De Lange, 2015;De Lange et al, 2015;Kooij et al, 2015), but no study to date has actually presented an overview of previous empirical work on the relationships between age conceptualizations and employability to draw more firm conclusions. Moreover, given the fact that previous scholarly efforts on aging at work and employability are limited and conceptually diverse (see also Kooij et al, 2008;Dikkers et al, 2017), we argue that it is important to incorporate multiple age conceptualizations, besides only calendar age (see also Le Blanc et al, 2017;Zacher et al, 2018).…”
mentioning
confidence: 99%
“…Earlier research has suggested that lifespan changes, like decreasing mental as well as physical reserves, can significantly affect the reported levels of employability (Brooke and Taylor, 2005;Ng and Feldman, 2009;Vandenberghe et al, 2012;Nilsson and Ekberg, 2013;Rusanova, 2014;Bal and De Lange, 2015;De Lange et al, 2015;Kooij et al, 2015), but no study to date has actually presented an overview of previous empirical work on the relationships between age conceptualizations and employability to draw more firm conclusions. Moreover, given the fact that previous scholarly efforts on aging at work and employability are limited and conceptually diverse (see also Kooij et al, 2008;Dikkers et al, 2017), we argue that it is important to incorporate multiple age conceptualizations, besides only calendar age (see also Le Blanc et al, 2017;Zacher et al, 2018).…”
mentioning
confidence: 99%